Optimal design of a tunable electromagnetic shunt damper for dynamic vibration absorber - Sun, Ruqi; Wong, Waion; Cheng, Li (Mechatronics (Oxford), 2022)
Dynamic vibration absorber (DVA) is an effective device for suppressing resonant vibration of noisy machineries and structures. However, the optimum design of DVA requires precise tuning of the damping force in the DVA, which unfortunately is often not practical and prone to changes of working conditions. In this paper, a tunable electromagnetic shunt damper (EMSD) with different opposing magnet pairs configurations is tested for the optimum design of DVA. The optimum magnet pairs configuration is derived to provide the maximum damping force in the DVA. Both simulations and experiments are conducted to verify the damping coefficient variation with the number of magnet pairs in the EMSD. The experimental optimization procedure of the DVA is designed according to the fixed-points theory. The damping force generated by the EMSD can be readily adjusted by varying the external resistance of the EMSD. This is the first experimental implementation report of the optimization procedure described in the fixed-points theory. The proposed tunable EMSD can conveniently allow for onsite optimal tuning of DVA. The proposed design methodology provides fine tuning of the damping coefficient of EMSD to achieve robust optimal DVA performance, even when subject to changes of external parasitic damping.